2020
DOI: 10.1038/s41598-020-68093-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Astragalus membranaceus in the treatment of laryngeal cancer based on gene co-expression network and molecular docking

Abstract: Astragalus membranaceus (HUANG QI, HQ) is a kind of traditional Chinese medicine. Researchers have widely concerned its antitumor effect. At present, there is still a lack of research on the treatment of laryngeal cancer with HQ. In this study, we integrated data from the weighted gene co-expression network of laryngeal cancer samples and the components and targets of HQ. A new method for dividing PPI network modules is proposed. Important targets of HQ treatment for laryngeal cancer were obtained through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…These key genes are not only the potential targets of Yixinyin, but also closely related to MI. Compared with the direct construction of Yixinyin PPI network, this method can better integrate the transcriptome data of the disease, making the research results more concentrated 38 . Admittedly, our approach also has a certain limitation.…”
Section: Discussionmentioning
confidence: 99%
“…These key genes are not only the potential targets of Yixinyin, but also closely related to MI. Compared with the direct construction of Yixinyin PPI network, this method can better integrate the transcriptome data of the disease, making the research results more concentrated 38 . Admittedly, our approach also has a certain limitation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used a network pharmacological approach to explore the material basis and molecular mechanisms of Astragalus membranaceus for the treatment of EC. Dong et al (2020) studied Astragalus membranaceus against laryngeal cancer through network pharmacology, showing that quercetin, rutin, and chlorogenic acid in Astragalus membranaceus are the main compounds that exert anti-cancer effects. Research by Liu et al (2019c) showed that 7-O-methyl iso-mucronulatol, quercetin, 3,9-di-O-methylnissolin, isorhamnetin, and formononetin in Astragalus membranaceus could activate the immune system to fight diseases by regulating the T cell immune response, the tropism of macrophages and the production of antimicrobial peptides.…”
Section: Discussionmentioning
confidence: 99%
“…The results of MDA showed that quercetin, rutin, and CGA can bind to MMP-1, MMP-3, and MMP-10 [ 140 ]. MDA of CGA and carbonic anhydrase IX showed the high affinity which is attributable to the strong interaction with enzyme active site through the formation of eight hydrogen bonds with the active site residue [ 141 ].…”
Section: Anti-cancer Effects Of Coffeementioning
confidence: 99%